Rare Diseases: Psychological Aspects Related to Preimplantation Genetic Testing in the Detection of Monogenic Diseases - Pérez, Susana Portela; Gutiérrez, Agustina Ramos; Cameselle-Cortizo, Lucía; Varela, María Ojeda; Rodríguez-Fernández, Vanesa; Cameselle-Teijeiro, Jorge F. (British Journal of Healthcare and Medical Research, 2025)
Preimplantation Genetic Testing for Monogenic Disorders (PGT-M) offers families affected by rare genetic conditions a powerful tool to prevent the transmission of severe inherited diseases. However, the psychological journey associated with this process is often complex and emotionally intense. This article explores the emotional experiences, ethical dilemmas, and decision-making challenges faced by couples who pursue PGT-M, particularly when there is a known family history of rare disorders. Drawing from clinical experience and current literature, we highlight the importance of clear communication, comprehensive genetic counseling, and continuous psychological support throughout the fertility journey. Addressing issues such as anxiety, guilt, partner dynamics, and expectations management can significantly improve outcomes and emotional well-being. As advances in genetic testing become more accessible, healthcare professionals must be prepared to accompany patients not only through the medical process but also through the emotional and ethical landscape that PGT-M entails.